PENGARUH LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. VARASH INDONESIA JAYA - Ni Luh Widyantari; I Wayan Suarjana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
High employee work productivity can be obtained if employees have the desire to improve their capabilities, so that company goals will be carried out effectively and efficiently. High productivity is closely related to the work environment, motivation and work culture. This study aims to determine the effect of the work environment and work culture on the work productivity of production employees at PT. Varash Indonesia Jaya. This research was conducted at PT. Varash Indonesia Jaya using a population and sample of 80 employees as research respondents. The sampling technique used in this study is the census method. Data collection was carried out through interviews, documentation, observation and questionnaires. The data analysis technique used in this study was multiple linear regression analysis which was processed using SPSS version 23 software. Based on the results of the analysis, this study shows that the work environment has a positive and significant effect on work productivity at PT. Varash Indonesia Jaya. The better the working environment at PT. Varash Indonesia Jaya, the better work productivity. Work culture has a positive and significant effect on work productivity at PT. Varash Indonesia Jaya. The decreasing work culture in PT. Varash Indonesia Jaya, work productivity will increase.